Investigation of Process Parameter of EDM using Genetic Algorithm (GA) Approach for Carbon Fiber based Two Phase Epoxy composites. (2016) - Mausam, Kuwar; Kumar Singh, Pradeep; Sharma, Kamal; Gupta, R.C.
Abstract: In this work Genetic Algorithm (GA) Approach is used for the optimization of the major process parameter of Electric Discharge machining (EDM). GA is used to determine the optimal level of process parameter of EDM during machining of Carbon fiber based two phase epoxy composite. Tool wear rate (TWR) and Material Removal Rate (MRR) are two input variable. Peak current (Ip ), gap voltage (Vg ), pulse-on-time (Ton ) and duty cycle (η) are considered as the four major parameter. In this work effect of these parameters are calculated on the TWR. MATLAB is used for the better convergence of GA. GA is run for 15 generations using MATLAB 2010 and the algorithm is converged to the objective function value of 0.0000125. TWR is decreased to 70% using the optimum values of parameters.